2019
DOI: 10.15252/embr.201948075
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular microRNA 130b‐3p inhibits eCIRP‐induced inflammation

Abstract: Although microRNAs regulate mRNA expression intracellularly, they are often released into the circulation in inflammatory diseases. During sepsis, secreted extracellular cold-inducible RNAbinding protein (eCIRP) acts as a damage-associated molecular pattern (DAMP), inducing tissue damage by elevating inflammatory cytokines and chemokines. Here, we report that the circulating microRNA 130b-3p inhibits eCIRP-mediated sterile and cecal ligation and puncture (CLP)-induced non-sterile inflammation. We find that lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 53 publications
(147 reference statements)
2
64
0
Order By: Relevance
“…The high intracellular concentrations of miR-BF1-5p and miR-BF2-5p [8] may be a prerequisite (or at least an advantage) for extracellular functions (e.g., in the form of free or exosome-associated miRNAs with local or systemic effects) [61]. For instance, it has recently been shown that under conditions of bacterial sepsis, the extracellular form of the murine and human miR-130b-3p is released into the blood and interacts, thereby attenuating the pro-inflammatory function of CIRP (cold-inducible RNA binding protein), a ligand of TLR4-mediated innate inflammatory signaling [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…The high intracellular concentrations of miR-BF1-5p and miR-BF2-5p [8] may be a prerequisite (or at least an advantage) for extracellular functions (e.g., in the form of free or exosome-associated miRNAs with local or systemic effects) [61]. For instance, it has recently been shown that under conditions of bacterial sepsis, the extracellular form of the murine and human miR-130b-3p is released into the blood and interacts, thereby attenuating the pro-inflammatory function of CIRP (cold-inducible RNA binding protein), a ligand of TLR4-mediated innate inflammatory signaling [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are abundant in microRNAs (miRNAs), small non-coding RNAs which regulate gene expression (44,47). Dysregulated miRNAs in sepsis patients include, but not limited to, miR-25, miR-130b-3p, miR-133a, miR-146, miR-150, and miR-223 (48,49). MiR-146 and miR-155 are well-characterized miRNAs induced by proinflammatory stimuli such as LPS and linked to TNF-α production (50).…”
Section: Extracellular Rnasmentioning
confidence: 99%
“…Wild-type (WT) and CIRP −/− mice were subjected to polymicrobial sepsis by cecal ligation and puncture (CLP). 30,34,35 Mice were anesthetized with 2% isoflurane inhalation. The abdomen was shaved and made sterile with 10% povidone-iodine wash. After a 1 cm midline abdominal incision, the cecum was exposed and ligated at 1 cm from the tip with 4-0 silk suture.…”
Section: Mouse Model Of Sepsismentioning
confidence: 99%
“…However, we showed that stimulation of freshly isolated BMDNs with rmCIRP significantly increased the percentage of Ly6G + CD11b hi LDNs. In sepsis, because the eCIRP level is elevated in the circulation,27,34 the circulatory eCIRP may directly induce the generation of Ly6G + CD11b hi LDNs in the blood. In the flow cytometry gating, there might be some CD11b lo cells overlapping with the CD11b hi population.…”
mentioning
confidence: 99%